α-Lipoic Acid Maintains Brain Glucose Metabolism via BDNF/TrkB/HIF-1α Signaling Pathway in P301S Mice - Zhang, Yan-hui; Yan, Xin-zhu; Xu, Shuang-feng; Pang, Zhong-qiu; Li, Lin-bo; Yang, Yang; Fan, Yong-gang; Wang, Zhuo; Yu, Xin; Guo, Chuang; Ao, Qiang (Frontiers in Aging Neuroscience, 2020)
Microtubule-associated protein tau is closely correlated with hypometabolism in Alzheimer’s disease (AD). α-lipoic acid (LA), which is a naturally occurring cofactor in mitochondrial, has been shown to have the properties which can inhibit the tau pathology and neuronal damage in our previous research. However, if LA has effect on glucose metabolism when it reverses tau pathology remains unclear, especially with respect to the potential mechanism. Therefore, we make a further study using P301S mouse model (a tauopathy and AD mouse model which overexpressing fibrillary tau) to gain a clear idea of aforementioned problems. Here, we found chronic LA administration significantly increased glucose availability by elevating glucose transporter 3 (GLUT3), GLUT4, vascular endothelial growth factor (VEGF) protein and mRNA level, and heme oxygenase-1 (HO-1) protein level in P301S mouse brains. Meanwhile, we found that LA also promoted glycolysis by directly upregulating hexokinase (HK) activity, indirectly by increasing proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) and DNA repair enzymes (OGG1/2 and MTH1). Further, we found the underlying mechanism of restored glucose metabolism might involve in the activation of brain-derived neurotrophic factor (BDNF)/ tyrosine Kinase receptor B (TrkB)/ hypoxia-inducible factor-1α (HIF-1α) signaling pathway by LA treatment.